Interaction of Oligonucleotides with Gold Nanoparticles: Factors Beyond Electrostatic and Van‐Der Waals Forces - Shaila Thakur; Nicola Cavallini; Debora Ferrari; Laura Fabris (Advanced Materials Interfaces)
Abstract Motivated by the development of direct SERS for the detection of oligonucleotides as disease biomarkers, fundamental study is conducted for the adsorption of short model oligonucleotides onto gold nanoparticles (GNPs). It is observed that the variation in solution conditions has a profound effect on the way in which oligonucleotides bind to GNPs. The binding phenomenon is hypothesized to be a contribution of several factors: base composition, strand directionality, competition of oligonucleotides to bind to GNPs or undergo inter‐strand assembly, among others. In addition to these factors, the properties of the individual bases in the given solution conditions (such as protonation or deprotonation) also affect the way in which the oligonucleotide strand binds to GNPs. In future, using this understanding could aid in developing direct SERS‐based sensing methods for disease detection through identification of mutations in genetic biomarkers of disease. Based on the present hypothesis, knowledge gaps to fill and future research directions are suggested, to better understand these adsorption processes and optimize direct SERS biosensing.